Effect of Iron Deficiency on Glycation of Haemoglobin in Nondiabetics - Balasubramanian, Shanthi; Carnagarin, Revathy; Arcot, Jagdeeshwaran Manjula; Subhashree, Subhashree (Premchand Shantidevi Research Foundation, 2013)
Background: Protein glycation is a spontaneous reaction that is believed to play a key role in the pathogenesis of many clinical disorders. The glycation of proteins is enhanced by elevated glucose concentrations. The major form of protein glycation with a clinical consideration is glycated haemoglobin (HbA1c). The HbA1c fraction is abnormally elevated in chronic hyperglycaemic diabetic patients and it correlates positively with the glycaemic control. However, increased glycated haemoglobin levels have been documented in iron deficiency anaemic patients without any history of diabetes. Aims and Objective: The aim of this study was to determine the effect of IDA on the HbA1c levels in nondiabetic patients, so as to consider IDA as an important factor which influenced the HbA1c levels, while monitoring the glycaemic status of diabetics. Methodology: Fifty non-diabetic, anaemic patients and 50 age-matched healthy subjects were enrolled in this study. The patients who had glucose tolerance abnormalities (impaired glucose tolerance or diabetes mellitus), haemoglobinopathies, haemolytic anaemia, infestation, chronic alcohol ingestion and chronic renal failure were excluded from the study. Haematologic investigations were done and the fasting and postprandial glucose and HbA1c levels were measured in all the subjects.Results: The mean HbA1c (7.6 ± 0.5%) level in the patients with IDA was higher than that in the control group (5.5% ± 0.8) (p < 0.001). There were no differences in the levels of fasting and postprandial glucose between the IDA and the control groups (p > 0.05). The haemoglobin, serum ferritin, fasting and postprandial glucose, and the HbA1c levels were normal in the control group (p > 0.05).Conclusion: HbA1c is not affected by the blood sugar levels alone, and there are various confounding factors when HbA1c is measured, especially that of iron deficiency, which is the commonest of the deficiency diseases worldwide. It is hence prudent to rule out IDA before making a therapeutic decision, based on the HbA1c levels.